Identity Formation, Marijuana and “The Self”: A Study of Cannabis Normalization among University Students - Mostaghim, Amir; Hathaway, Andrew D. (Frontiers in Psychiatry, 2013)
Over the past half-century, as use of marijuana has become more widespread in Canadian society, there are indications of a normalizing process in societal reactions and experiences of use. Among other research avenues, these trends suggest a need for further exploration of young people’s understandings of how they make the choice to use or not and how decisions relate to presentation of the self. This study draws on interviews with 30 undergraduates recruited from a larger on-line survey of respondents at the University of Guelph, Ontario, Canada. In probing their perceptions of the use of marijuana, we often found that trying/using ‘pot’ was the default option, whereas choosing not to use required more conscious effort. With specific reference to Goffman’s contribution to a situated understanding of the self, our findings are interpreted with emphasis on further theoretical development of the normalization thesis and on the role of marijuana in identity formation among persons in the process of transition to adulthood.